2022
DOI: 10.1177/07334648221124913
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Increasing State Minimum Wage on Family and Paid Caregiving

Abstract: Older adults may receive either or a combination of unpaid family/friend and paid caregiving. The consumption of family/friend and paid caregiving may be sensitive to minimum wage policies. We used data ( n = 11,698 unique respondents) from the Health and Retirement Study and a difference-in-differences design to evaluate associations between increases in state minimum wage between 2010 and 2014 and family/friend and paid caregiving consumed by adults age 65+ years. We also examined responses to increases in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…30 A recent study found that state MW increases were not associated with higher utilization of paid home care services among older residents with dementia. 31 MW policies would not increase the use of home care if the policy did not increase employment. Given the market shortage of home health aides, home health employers may have to recruit workers from other industries.…”
Section: Discussionmentioning
confidence: 99%
“…30 A recent study found that state MW increases were not associated with higher utilization of paid home care services among older residents with dementia. 31 MW policies would not increase the use of home care if the policy did not increase employment. Given the market shortage of home health aides, home health employers may have to recruit workers from other industries.…”
Section: Discussionmentioning
confidence: 99%